On the reproduction of gender inequality in the premium effect of the Internet on wage: A case study based on data from the Chinese Women's Status Survey (third phase). (January 2018) - Zhuang, Jiachi; Liu, Aiyu; Sun, Chao
By using the Propensity Score Matching model, this study proves the existence of an Internet premium effect. After other factors are controlled, it is found that the average wage income of Internet users is 1.38 times that of non-users. At the same time, there are significant gender differences in the premium effect of the Internet on wages: Women's Internet wage premium is 90.6% that of men. Furthermore, it is found that the Internet premium effect on wages is highly related to users' online behaviors. Compared with female users, male users are more inclined to use Internet resources to acquire knowledge and human capital; among female users, those with a greater conception of gender equality are more inclined to use the Internet for learning and accumulation of human capital. Using the framework of previous research on gender inequality in cyberspace, this study focuses on how gender perception influences Internet users' preferences and ways of using the Internet, which is an important cause and mechanism of reproduction of gender inequality in cyberspace.